Graphene Mesh for Self‐Sensing Ionic Soft Actuator Inspired from Mechanoreceptors in Human Body. Issue 23 (11th October 2019) - Tabassian, Rassoul; Nguyen, Van Hiep; Umrao, Sima; Mahato, Manmatha; Kim, Jaehwan; Porfiri, Maurizio; Oh, Il‐Kwon
Abstract: Here, inspired by mechanoreceptors in the human body, a self‐sensing ionic soft actuator is developed that precisely senses the bending motions during actuating utilizing a 3D graphene mesh electrode. The graphene mesh electrode has the permeability of mobile ions inside the ionic exchangeable polymer and shows low electrical resistance of 6.25 Ω Sq −1, maintaining high electrical conductivity in large bending deformations of 180°. In this sensing system, the graphene woven mesh is embedded inside ionic polymer membrane to interact with mobile ions and to trace their movements. The migration of mobile ions inside the membrane induces an electrical signal on the mesh and provides the information regarding ion distribution, which is proven to be highly correlated with the bending deformation of the actuator. Using this integrated self‐sensing system, the responses of an ionic actuator to various input stimulations are precisely estimated for both direct current and alternating current inputs. Even though the generated displacement is extremely small around 300 µm at very low driving voltage of 0.1 V, high level accuracy (96%) of estimated deformations could be achieved using the self‐sensing actuator system. Abstract : A graphene mesh electrode having high ion permeability and electrical conductivity is adopted as a self‐sensing ionic soft actuator inspired by mechanoreceptors in the human body. The graphene mesh electrode provides electrical signals sensitive to ion migration inside the polymer electrolyte without blocking their movements and is used to predict the bending deflection of the actuator.